Antimicrobial Resistance and Virulence Gene Profiles of Methicillin-Resistant and -Susceptible Staphylococcus aureus From Food Products in Denmark - Li, Heng; Andersen, Paal Skytt; Stegger, Marc; Sieber, Raphael N.; Ingmer, Hanne; Staubrand, Nicholas; Dalsgaard, Anders; Leisner, Jørgen J. (Frontiers in Microbiology, 2019)
Foods may potentially serve as vehicles for transmission of antimicrobial-resistant variants of Staphylococcus aureus that are important in a human clinical context. Further, retail food products can be a cause of staphylococcal food poisoning. For these reasons and to account for source attribution and risk assessment, detailed information on the population structure, resistance and virulence profiles of S. aureus originating from retail food products is necessary. In the current study, whole-genome sequences from 88 S. aureus isolates were subjected to bioinformatics analyses in relation to sequence types, antimicrobial resistance, and virulence profiles. Thirteen clone complex types were determined in these food products with the most commonly detected clonal lineages being clonal complex CC5 and CC398. CC398 were identified as the dominant clone (n=31). CC5 were identified as of avian origin with the presence of φAVβ prophage genes (n=13). Totally 39.8% of the isolates contained multiple resistance genes and MRSA isolates were found in CC8, CC9, and CC398. Genes conferring resistance to the antimicrobial classes of β-lactams, tetracycline, and erythromycin were detected in this study, all of which are commonly used in Danish livestock production. The tst gene encoding the toxic shock syndrome toxin was for the first time identified in ST398 isolates, probably as a result of a single acquisition of a SaPI-like element. The sushi-CC398 isolates carrying the scn gene likely originated from a human reservoir while the other isolates originated from livestock. Taken together, our results show that both human and animal reservoirs contribute to contaminations in food products and retail foods may serve as a vehicle of S. aureus between livestock and humans.